Exchange Rate, Gold Price, and Stock Market Nexus: A Quantile Regression Approach - Rizwan Ali; Inayat Ullah Mangla; Ramiz Ur Rehman; Wuzhao Xue; Muhammad Akram Naseem; Muhammad Ishfaq Ahmad (Risks, 2020)
In this study, we examine an empirical relationship between stock market volatility with the exchange rate and gold prices of an emerging market, “Pakistan”, employing daily and monthly data (PSX-100 Index) covering from 2001: Q3 to 2018: Q2. The study explains the average stock returns by applying MGARCH. Further, it investigates that the volatility in the exchange rate (Rs/US $) and gold prices remain equally strong in bearish and bullish conditions of the stock market by using a quantile regression approach (2001–2018). Additionally, the sample period is divided into two split samples that cover (2001–2007) and (2008–2018) respectively, based on global financial crises and applied similar analysis. The overall results show the negative impact of the exchange rate and gold price volatility on the stock market performance daily (monthly), supporting the argument that the stock market considers the exchange rate and gold price fluctuations as an adverse indicator and reacts negatively.